Towards scalable plasmonic Fano-resonant metasurfaces for colorimetric sensing. (1st October 2022) - Cerjan, Benjamin; Gerislioglu, Burak; Link, Stephan; Nordlander, Peter; Halas, Naomi J; Griep, Mark H
Abstract: Transitioning plasmonic metasurfaces into practical, low-cost applications requires meta-atom designs that focus on ease of manufacturability and a robustness with respect to structural imperfections and nonideal substrates. It also requires the use of inexpensive, earth-abundant metals such as Al for plasmonic properties. In this study, we focus on combining two aspects of plasmonic metasurfaces—visible coloration and Fano resonances—in a morphology amenable to scalable manufacturing. The resulting plasmonic metasurface is a candidate for reflective colorimetric sensing. We examine the potential of this metasurface for reflective strain sensing, where the periodicity of the meta-atoms could ultimately be modified by a potential flexion, and for localized surface plasmon resonance refractive index sensing. This study evaluates the potential of streamlined meta-atom design combined with low-cost metallization for inexpensive sensor readout based on human optical perception.